BLOOD PRODUCT SAFETY - Putri, Widaninggar Rahma (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Palembang, 2022)
Background: Blood transfusion services are attempted to utilize human blood as a basic element for humanitarian purposes. Both blood and blood products are playing a crucial role in health services. Blood transfusion is a medical procedure that contains risks due to the possible risk of Blood-transfusion related infectious disease. Each blood product is requisite to be screened for blood-transfusion related infectious disease at least in 4 parameter such as Hepatitis B Surface Antigen (HBsAg), HIV 1/ HIV 2 Antibody, Hepatitis C antibody (anti-HCV) and Syphilis. Blood-transfusion related Infectious disease can be detected through antibody or antigen detection by various methods such as Chemiluminescence Immuno Assay (CLIA). Methods: This paper is a literature review, Results: CLIA has been developed in various field including clinical diagnosis of various disease due to its selective, sensitive, speedy and short time analysis time consuming. Conventional immunoassay methods requires longer incubation time, longer turnaround time and shorter detection range. Conclusion:CLIA can be used to reduce examination time while increasing its sensitivity and spesificity.